DIVERSITY DYNAMICS OF FUSULINID GENERA AND MAIN STAGES OF THEIR EVOLUTION - Leven E.Ya. (My University, 2003)
Curves depicting the diversity dynamics of fusulinid genera in general and in some individual biogeographic provinces are provinces are plotted. Some of them illustrate dynamics of appearance and extinction of fusulinid genera and orders. As is evident from the curves, there were three major stages in the fusulinid evolution, each beginning with the diversity increase (the Moscovian, Asselian and Midian peaks) and ending with the diversity minimum (the early Gzhelian, late Kungurian, and late Dorashamian minima). In addition to three major stages, several second-order stages can be distinguished. The diversity peaks were likely associated with extensive transgressions, which might enlarge the habitat areas of fusulinids, thus favoring appearance of new taxa adapted to different environments, and represented the main controlling factor. These peaks were followed by extinctions, the greatest of which took place in the late Moscovian, post-Sakmarian, late Kungurian, late Midian, and late Dorashamian eppochs. The latter two were of catastrophic character: Nearly 80% of fusulinid genera became extinct in the late Midian and all others in the late Dorashamian time. The extinctions mostly affected the highly specialized taxa far advanced in their evolution. The origin of new elements in the assemblages that replaced the disappearing ones was confined to crises in the fusulinid evolution.
Keywords: Paleozoic::Permian::Cisuralian; Палеозой::Пермская::Приуральский